Clinical and Immune Responses of Peripheral Chemical Sympathectomy in Enterovirus 71 Infection - Liao, Yu-Ting; Tsai, Huey-Pin; Wang, Shih-Min; Chen, Shun-Hua (Frontiers in Immunology, 2021)
The activation of the sympathetic nervous system, release of norepinephrine (NE), and adrenergic receptor signaling participate in and regulate the complicated enterovirus 71 (EV71) brainstem encephalitis (BE). The neurotoxin 6-hydroxydopamine (6-OHDA) selectively ablates sympathetic nerves and markedly depletes NE in innervated organs. Changes in the plasma levels of NE, severity score, cytokine profiles, and percentages of immunophenotype expression in 7-day-old Bltw:CD1 (ICR) mice infected with EV71, with or without 6-OHDA treatment, were compared. The survival rate (76.9%) of EV71-infected and 6-OHDA (30 μg/g)-treated mice was increased significantly. The clinical scores were decreased markedly on days 8-12 in MP4-infected and 6-OHDA-treated mice compared to those without treatment. The results showed that the plasma levels of NE, epinephrine, and dopamine were decreased on days 4–8 after 6-OHDA treatment and at most on day 8. The plasma levels of interleukin (IL)-12p70, tumor necrosis factor, IL-6, and IL-10 did not change significantly after 6-OHDA treatment. Interferon- levels decreased evidently on days 4, 6, and 8 after 6-OHDA treatment. The absolute events of CD3+CD4+, CD3+CD8+, and CD3+NK1.1+ cells of peripheral blood mononuclear cells were increased significantly in MP4-infected and 6-OHDA-treated mice compared to those without treatment. In splenocytes, the absolute cells of CD3−NK1.1+ and, CD3+NK1.1+ and CD11b+Gr-1+ cells of EV71-infected mice were increased significantly after 6-OHDA treatment. These findings suggested that 6-OHDA may be used a probe to explore clinical improvements and immune responses in the complicated EV71 infection. Taken together, peripheral chemical sympathectomy These properties together contribute to further understand the immunopathogenesis of EV71 BE with autonomic nervous system dysregulation.